2022
DOI: 10.3389/fphar.2022.845221
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum RH2 Alleviates Chronic Foot Shock Stress-Induced Behavioral Deficits in Rats via PAI-1

Abstract: Recent investigations have demonstrated that the chronic stress-induced behavioral disorders can be ameliorated by probiotics including Clostridium butyricum (C. butyricum) via the gut-brain-axis. However, the molecular mechanisms underlying the beneficial effects of C. butyricum on brain remain largely unknown. Here, we investigated whether chronic foot shock stress (CFSS) paradigm used for a hypertensive animal model could induce mood disorders such as anxiety, depression and cognitive impairments. Then, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Fibrinolytic enzymes are converted from fibrinogen in the presence of tissue plasminogen activator, which can be inhibited by plasminogen activator inhibitor-1 (PAI-1), leading to the accumulation of pro-BDNF. Previous studies found that PAI-1 increases in the prefrontal cortex and hippocampus of chronically stressed rats (Party et al, 2019;Zhang W. et al, 2022). The decreased BDNF can be found in patients with depression (Jiang et al, 2015;Youssef et al, 2018), whereas antidepressant treatment can increase the levels of BDNF (Martinotti et al, 2016).…”
Section: Decreased Level Of Bdnfmentioning
confidence: 94%
See 2 more Smart Citations
“…Fibrinolytic enzymes are converted from fibrinogen in the presence of tissue plasminogen activator, which can be inhibited by plasminogen activator inhibitor-1 (PAI-1), leading to the accumulation of pro-BDNF. Previous studies found that PAI-1 increases in the prefrontal cortex and hippocampus of chronically stressed rats (Party et al, 2019;Zhang W. et al, 2022). The decreased BDNF can be found in patients with depression (Jiang et al, 2015;Youssef et al, 2018), whereas antidepressant treatment can increase the levels of BDNF (Martinotti et al, 2016).…”
Section: Decreased Level Of Bdnfmentioning
confidence: 94%
“…In fact, recent findings suggest that probiotics may improve host health in patients with IBS both physically and mentally (Le Morvan De Sequeira et al, 2021;Zhang T. et al, 2022). The safety and efficacy of probiotics in the treatment of IBS are supported by numerous clinical studies.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
See 1 more Smart Citation